The Gut Microbiome of 54 Mammalian Species - de Jonge, Nadieh; Carlsen, Benjamin; Christensen, Mikkel Hostrup; Pertoldi, Cino; Nielsen, Jeppe Lund (Frontiers in Microbiology, 2022)
The gut microbiome plays a critical role in many aspects of host life, and the microbial community composition is heavily influenced by the prevailing conditions in the gut environment. The community composition has been suggested to have large implications for conservation efforts, and gut health has become of interest for optimising animal care in captivity. In the present study we explore the gut microbiome of a wide range of animals in the context of conservation biology. The gut microbial community composition of 54 mammalian animal species was investigated using 16S rRNA gene amplicon sequencing. The composition of the gut microbiota clearly reflected the diet and the structure of the gastrointestinal system, and is to a certain degree more similar between closely related animals. Specific clusters of taxa were observed across animals of the same species, diet and digestive physiology. The microbiota retained regardless of captivity status is hypothesized to cover important symbiotic relationships with the host, while the remaining part reflects the artificial living conditions and can therefore be used as a future tool for conservation biologists. For five animal species (giraffes, horses, baboons, elephants and zebras) it was possible to compare the microbiota of wild and captive individuals. Differences were observed in the proportion of microbiota detected between wild and captive specimens of the same animal species. We propose that the gut microbiota harbour important species, which can potentially serve as indicators for the well-being of the animal and the effect of living in captivity.